Integrated stratigraphy, facies analysis and correlation of the upper Albian–lower Turonian of the Esfahan area (Iran): Unravelling the conundrum of the so-called "Glauconitic Limestone". (October 2018) - Hairapetian, Vachik; Wilmsen, Markus; Ahmadi, Amir; Shojaei, Ziba; Berensmeier, Michaela; Majidifard, Mahmoud Reza
Abstract: The so-called "Glauconitic Limestone of Esfahan" is a thin (<4 m) but very conspicuous lithological unit that is well known for its late Albian to middle Cenomanian ammonite faunas. However, it consists of two genetically unrelated stratigraphical units: the lower part commonly comprises fine-grained bioclastic limestones that are poor in macrofossils and rest with a sharp basal surface on mid-upper Albian strata of the deep-marine Bazyab Formation; the microbiostratigraphy shows this part to be mid-late Albian in age ( Pseudothalmanninella ticinensis Zone), thus constituting a lithostratigraphical equivalent of the lower Debarsu Formation. The upper part of the "Glauconitic Limestone" consists of a fossiliferous glauconitic conglomerate with large rounded limestone pebbles to boulders and phosphatized bio-/lithoclasts, yielding the famous ammonite faunas of the unit. It has a major erosional unconformity at its base that may cut out the Debarsu Formation over short distances and it shows a fining-upward trend grading into an overlying marl and argillaceous limestone unit. These observations demonstrate that the glauconitic conglomerate initiated a new depositional cycle and is thus genetically related to the overlying fine-grained strata. Consequently, the glauconitic conglomerate is regarded as the basal Takhte-Sheitan Member (new) of the Kolah-Qazi Formation (new), formalized herein. The matrix of the upper part of the Takhte-Sheitan Member could be dated as mid-late Cenomanian (upper Rotalipora cushmani Zone) and the overlying fine-grained offshore deposits of the Kolah Qazi Formation as latest Cenomanian to early Turonian by means of foraminifera, ammonites, inoceramid bivalves and carbon stable isotopes. Thus, the late Albian to middle Cenomanian phosphatized ammonites from the Takhte-Sheitan Member are derived, i.e., represent classic remanié faunas. The Takhte-Sheitan Member is regarded as a complex, condensed transgressive lag onlapping a considerable palaeotopography after a late mid- to early late Cenomanian tectonic event. The overlying marl and argillaceous limestones of the Kolah-Qazi Formation indicate a considerable deepening in response to a major eustatic sea-level rise and highstand across the Cenomanian–Turonian boundary associated by increased organic carbon burial related to the oceanic anoxic event (OAE) 2. The carbon stable isotope curve from the base of the Kolah-Qazi Formation (Takhte-Sheitan Member) up-section into the marls and argillaceous limestones shows the conspicuous structure of the major positive excursion of the OAE 2 and serves as precise tool for the high-resolution chemostratigraphic calibration of the Iranian sections. It provides a new reference curve for the OAE 2 in the Middle East. Highlights: The "Glauconitic Limestone of Esfahan" consists of two stratigraphically and genetically unrelated units. Its lower mid-upper Albian part represents an erosional remnant of the Debarsu Formation. Its upper part, mid-late Cenomanian in age, corresponds to the Takhte-Sheitan Member of the overlying Kolah-Qazi Formation (new). The well-known late Albian to middle Cenomanian ammonites from the transgressive Takhte-Sheitan Member are phosphatized remanié faunas. A carbon stable isotope curve straddling the OAE 2 has been established and correlated to reference sections on different continents.